Iran’s Long Reach: Iran as a Pivotal State in the Muslim World by Suzanne Maloney (Washington, DC: United States Institute of Peace Press, 2008. 156 pages.) (American Journal of Islam and Society, 2010)
This short analytical book attempts to serve American decision-maker policychoices with respect to the “pivotal” country of Iran. The pivotal state thesishas sought to organize the United States’ national security strategy after thecollapse of the Soviet Union and the end of the cold war.1Maloney applies itto the Iranian case, given that country’s geostrategic value and significant rolein global issues and negotiations (pp. 4-5). She adopts the thesis’ mainassumption that by investing attention and resources in regional heavyweights,the United States can benefit from the “multiplier” effect of theirweight. Arguing that as the United States seeks to change its strategicapproach toward the region, the author posits that focusing on the Muslimworld’s pivotal states will help prioritize challenges and opportunities andthus better serve its vital interests (p. 5). She proceeds to do so by making thecase for Iran’s crucial importance while outlining what she perceives to be itspolitical, economic, security and theological dilemmas – presumably so thatWashington and its allies can take advantage of them.The study also attempts to examine the shifts from reformist (Khatami)toward more radical (Ahmadinejad) politics in Iran’s domestic scene. Shetraces the reasons why the Iranian “reform movement,” under Khatamifailed and attributes that outcome to self-imposed constraints (redlines), fearof bringing about instability, and the movement’s elitist structure (pp. 12-13). Maloney also points to Ahmadinejad’s “perverse” but “compelling”incentive to preserve the long-standing antagonism toward the UnitedStates. She expresses her concern that such shifts may serve to undermineany remaining international consensus necessary to address “problematicelements of Iran’s foreign policy” (p. 23) ...